Customer Satisfaction and Service Quality Assessment of Nepal Yatayat Public Buses: A Statistical Analysis of Passenger Perceptions - Singh, Balkrishna; Karki, Sujata (NPRC Journal of Multidisciplinary Research, 2024)
Background: Public transportation is vital for urban mobility, offering affordable and accessible commuting options, especially in densely populated regions. In Nepal, public buses serve a broad demographic, and understanding passenger satisfaction with services like Nepal Yatayat can provide insights for service improvements. Objective: This study aims to analyze customer satisfaction with the Nepal Yatayat bus service, examining factors such as comfort, safety, cleanliness, punctuality, and overall service reliability. The goal is to identify key areas for improvement to enhance user experience and promote public transport use. Methods: The study utilized a quantitative approach through a structured questionnaire distributed to 92 respondents. Data analysis was conducted using SPSS software, where various statistical tools such as correlation and reliability analysis assessed relationships between demographic factors and satisfaction variables. Findings: The majority of respondents were young adults aged 18-24 (75.8%), predominantly male (65.9%), with a significant portion holding bachelor’s degrees (49.5%) and most being unemployed (61.8%). 59.4% of respondents expressed discomfort with bus seating and internal space arrangements, while 78.1% reported dissatisfaction or uncertainty about cleanliness standards. About 42.9% felt safe on Nepal Yatayat buses, while 30.8% were dissatisfied with punctuality. 37.7% of respondents rated staff behavior poorly, indicating a need for improvement in professionalism. Overcrowding was a significant concern, with 67.1% agreeing that buses were frequently crowded, and 45.1% believed the bus station locations were appropriate. : Reliability was rated as medium by 77.2% of respondents, with moderate recommendations for the service among users (40.7% likely to recommend). Conclusion: The analysis reveals that Nepal Yatayat requires improvements in comfort, cleanliness, safety, and punctuality to enhance passenger satisfaction. Crowding and staff professionalism are also key areas where service modifications could significantly impact commuter perceptions. Novelty: This study provides a detailed and empirical assessment of passenger satisfaction specifically with Nepal Yatayat, addressing service dimensions such as comfort, cleanliness, safety, and route effectiveness, previously underexplored in public transport studies within Nepal.